STUDI ANALISIS SEDIMENTASI DI SUNGAI PUTE RAMMANG-RAMMANG KAWASAN KARST MAROS - Andirah Al Ansar; Muhammad Arsyad; Sulistiawaty Sulistyawaty (Jurnal Sains dan Pendidikan Fisika, 2014)
Research on sedimentation analysis in Pute river at Rammang-Rammang Maros Karst Region aims to calculate suspended load and bed load, describing sedimentation rate, and analyze the types of sediment contained in Pute river. Water samples of Pute River water were taken using by water sample sediment tool. Sampling was conducted at two points called the dock I (4 ° 55'59,02 " LS and 119 ° 35'51,69" BT) and dock II (4° 55' 30,01" LS and 119° 35' 27,77" BT). Water samples are then processed in Laboratory to determine the sediment concentration. The  data were analyzed with formulate for getting suspended load value and bed load value. Suspended load value and bed load value were analyzed to estimate in a tabulation manner to presume of total sedimentation rate. For analyzing a types of sediment with using a sieve method. From the sedimentation analysis in Pute river obtained results: To suspended load in the dock I ranged from 0,1104-5,9221 g/s and dock II ranged from 0,2156-4,4297 g/s. For bed load value of dock I ranged from 0,0793-5,3821 g/s and dock II ranged between 2,7307-106,6038 g/s. Total value of sedimentation on the dock I ranged between 0.1573-9,5096 g/s and dock II ranged between 3,3721-109,9574 g/s, so the sediment load in the pute river included in the high category in accordance with Letter of Decree by The Minister of Forestry in 2005. Characteristics of sediment crawl based on particle diameter, obtained for the dominant type of sedimentation dock I is a coarse gravel. As for the dock II is dominant types of medium sand..Penelitian tentang analisis sedimentasi di Sungai Pute Rammang-Rammang kawasan karst Maros bertujuan untuk menghitung besar debit muatan sedimen melayang dan dasar, mendeskripsikan tingkat sedimentasi, serta menganalisis jenis-jenis sedimen yang terdapat di Sungai Pute. Pengambilan sampel air dari Sungai Pute menggunakan alat water sampler sediment. Ada 2 titik pengambilan sampel yang disebut dermaga I (4°55’59,02” LS dan 119°35’51,69” BT) dan dermaga II (4°55’30,01” LS dan 119°35’27,77” BT), kemudian sampel air diolah di laboratorium untuk menentukan konsentrasi sedimen. Data-data dianalisis secara formula untuk mendapatkan nilai besar debit muatan sedimen melayang dan debit muatan sedimen dasar, kemudian dianalisis secara tabulasi untuk mengetahui besar sedimentasi total, selain itu untuk menganalisis jenis-jenis sedimen digunakan metode ayakan dengan 7 sieve. Dari analisis sedimentasi di sungai Pute diperoleh hasil: debit muatan sedimen melayang di dermaga I berkisar 0,1104-5,9221 gram/s dan dermaga II berkisar 0,2156-4,4297 gram/s. Untuk debit muatan sedimen dasar di dermaga I berkisar 0,0793-5,3821 gram/s dan dermaga II berkisar antara 2,7307-106,6038 gram/s. Nilai sedimentasi total pada dermaga I berkisar antara 0.1573-9,5096 gram/s dan dermaga II berkisar antara 3,3721-109,9574 gram/s. Berdasarkan muatan sedimen total maka Sungai Pute termasuk dalam kategori tinggi sesuai SK Menteri Kehutanan Tahun 2005. Berdasarkan diameter partikelnya maka hasil karakteristik sedimen merayap pada dermaga I diperoleh dominan batu kerikil kecil, sedangkan untuk dermaga II dominan jenis sedimen pasir sedang.Kata Kunci:         sedimentasi, sieve net, Rammang-rammang, water sampler sediment